Psychological determinants of procrastination in the formation of students' independent learning activity - Razakov Farhod Kuvandikovich (Goodwood Publishing, 2025)
Purpose: This study aims to examine the psychological determinants of procrastination in the process of developing students’ independent learning activities. It focuses on how procrastination, as a conscious delay in task completion, is linked to academic motivation, self-regulation, and time management. Research Methodology: A qualitative-descriptive approach was employed, drawing on a review of contemporary psychological and educational literature. The analysis integrates cognitive, emotional, and social perspectives to understand the underlying causes of procrastination and its implications for independent learning. Results: The findings reveal that procrastination is strongly associated with deficits in time management skills, low intrinsic motivation, and poor emotional regulation. Social influences, such as peer pressure and learning environment, also play a significant role. These factors collectively hinder the effectiveness of independent learning by reducing persistence, focus, and academic achievement. Conclusions: Procrastination acts as a barrier to effective self-directed learning. Addressing cognitive distortions, fostering emotional resilience, and enhancing self-regulation are essential to reducing procrastination levels and improving independent learning outcomes. Limitations: The study is limited by its reliance on literature-based analysis rather than empirical testing. Future research should employ longitudinal and experimental designs to measure causal relationships between procrastination and learning effectiveness. Contribution: This article contributes to educational psychology by highlighting the interplay between psychological factors and learning behavior, offering practical recommendations to support students’ self-directed learning.